Temporal variability and annual budget of inorganic dissolved matter in Andean Pacific Rivers located along a climate gradient from northern Ecuador to southern Peru - Moquet, Jean Sébastien (2018)
In Ecuador and Peru, geochemical information from Pacific coastal rivers is limited and scarce. Here, we present an unedited database of major element concentrations from five HYBAM observatory stations monitored monthly between 4 and 10 years, and the discrete sampling of 23 Andean rivers distributed along the climate gradient of the Ecuadorian and Peruvian Pacific coasts. Concentration (C) vs. discharge (Q) relationships of the five monitored basins exhibit a clear dilution behavior for evaporites and/or pyrite solutes, while the solute concentrations delivered by other endmembers are less variable. Spatially, the annual specific fluxes for total dissolved solids (TDS), Ca²⁺, HCO₃, K+, Mg²⁺, and SiO₂ are controlled on the first order by runoff variability, while Cl, Na⁺ and SO₄² are controlled by the occurrence of evaporites and/or pyrite. The entire Pacific basin in Ecuador and Peru exported 30 Mt TDS·yr ¹, according to a specific flux of ∼70 t·km ²·yr ¹. This show that, even under low rainfall conditions, this orogenic context is more active, in terms of solute production, than the global average.